Efficacy of simultaneous VEGF‐A/ANG‐2 neutralization in suppressing spontaneous choroidal neovascularization - Richard H Foxton; Sabine Uhles; Sabine Grüner; Franco Revelant; Christoph Ullmer (EMBO Molecular Medicine, 2019)
Graphical Abstract This study independently confirms in vivo in the JR5558 mouse model of aberrant retinal angiogenesis, that simultaneous VEGF‐A and ANG‐2 neutralization using a bispecific anti‐VEGF‐A/ANG‐2 antibody reduces vascular leakage, immune reactivity and apoptosis more effectively than either agent alone.